A CHRNA5 Allele Related to Nicotine Addiction and Schizophrenia - Hong, L. Elliot (2011)
Schizophrenia and nicotine addiction are both highly heritable phenotypes. Because individuals with schizophrenia have a higher rate of smoking than those in the general population, one could hypothesize that genes associated with smoking might be over-represented in schizophrenia and thus help explain their increased smoking incidence. Although a number of genes have been proposed to explain the increased smoking risk in schizophrenia, none of them have been consistently linked to smoking and schizophrenia and thus difficult to explain the increased smoking in schizophrenia. A functional smoking-related nicotinic acetylcholine receptor α5 subunit gene (CHRNA5) nonsynonymous SNP rs16969968 (Asp398Asn) has recently been discovered and replicated. As such, we tested whether this variant contributes to smoking in schizophrenia in a sample of 313 schizophrenia patients and 525 controls. The Asp398Asn risk allele is significantly associated with smoking severity independently in schizophrenia patient smokers (p=0.001) and in control smokers (p=0.029). Furthermore, the same risk allele is significantly associated with schizophrenia in both Caucasian (p=0.022) and African American (p=0.006) nonsmoker schizophrenia patients compared to control nonsmokers. Intriguing, this SNP was not significantly associated with smoking status (smokers vs. nonsmokers) in either schizophrenia patients or controls. Therefore, our study identifies a genetic variant that is simultaneously linked to smoking and schizophrenia in the same cohort, but whether and how this SNP contributes to the increased smoking prevalence in schizophrenia patients requires additional studies.